Classification, Processing Procedures, and Market Demand of Chinese Biscuits and the Breeding of Special Wheat for Biscuit Making. (15th July 2022) - Hu, Xin; Hu, Lejia; Zheng, Jing; Rong, Junkang
Abstract : With the improvement of living standards, consumers' demand for wheat food is gradually diversified. Biscuit, as a kind of convenience food, becomes a consumer's leisure snack due to its characteristics such as low processing cost, easy-to-carry and convenient-to-eat traits, long shelf life, diverse varieties, and rich tastes, which have attracted more and more people. Biscuits are composed of four main ingredients, which are flour, fat/oil, sugar, and water, whereas several secondary ingredients also are important sources of high molecular carbohydrates, plant proteins, vitamins, and minerals for human beings. In this study, we systematically summarized the related research of biscuits, including the main types of China's biscuits, the market demands, and statistics of wheat planting, production, and import in recent ten years, as well as the research of soft wheat breeding for biscuit. The flour consumption of biscuit industry has been maintained at more than 4 million tons, accounting for more than 30% of the flour consumption in food industry. The planting area of wheat in China has stabilized around 22.8 million hectares in 2010–2020, while the yield of wheat has increased 18.0% (20.86 million t) due to the increase of yield per unit of wheat. China's total annual pastry import bill increased 5 times and the gap between import and export bill of pastry has been increased more than 7 times from 2010 to 2020, suggesting the strong demand of the national pastry market. This research also provides a direction for the future breeding of special soft wheat for biscuits in China.